High Spin Hall Conductivity Induced by Ferromagnet and Interface. (25th June 2022) - Li, Rongxin; Yuan, Xiaojuan; Tu, Huayao; Zhang, Zhenhua; Luo, Yanxiang; Chen, Qian; Li, Shangkun; Liang, Shiheng; Liu, Yong; Lu, Zhihong; Zeng, Zhongming; Xiong, Rui
Abstract: Spin‐orbit‐torque (SOT) offers a highly attractive perspective for manipulating magnetization dynamics in magnetic nanostructures. SOT is been observed and studied in various systems. However, limited by the efficiency, SOT‐induced switching of the ultrahard ferromagnet is still extremely difficult and a further improvement in efficiency is requested. Here, the SOT is reported in chemically disordered soft Fe0.5 Pt0.5 and Pt/Fe0.5 Pt0.5 bilayers. Due to the magnetization‐strengthened spin Hall effect, the damping‐like torque efficiency and spin Hall conductivity (SHC) in Fe0.5 Pt0.5 reach 1.11 and 1.08 × 10 6 ℏ /2 e  Ω −1 m −1 respectively, much higher than those in conventional materials. Furthermore, the Pt/Fe0.5 Pt0.5 interface enhances SHC to a total of 2.93 × 10 6 ℏ /2 e  Ω −1 m −1 due to the interfacial symmetry breaking. This system can be used to partially switch the magnetization of ultra‐hard exchange‐spring system with a switching field of 1T by applying a relatively low current. This finding will push forward the development of SOT devices with ultrahigh‐density and low‐power consumption. Abstract : Local magnetic moments enhance the spin Hall effect and result in over 1 damping‐like torque efficiency in well‐crystallized disorder FePt alloys. By the introduction of an adjacent Pt and interface, the total spin Hall conductivity can be further improved and even be used to switch the ultrahard perpendicular ferromagnet, providing a new method in spintronic application.